Morphological and molecular characterisation of the nematode parasite Graphidioides affinis (Secernentea: Trichostrongylidae) in Patagonian maras, Dolichotis patagonum, kept in a zoo in Sofia, Bulgaria - Panayotova-Pencheva Mariana; Laskowski Zdzisław; Pyziel Anna Maria (Journal of Veterinary Research)
Patagonian maras, rodents endemic to South America, are classified as a near-threatened species. Various factors affect their health including parasitic diseases. The aim of this study was to perform morphometric, molecular and phylogenetic characterisation of one such parasitic disease agent, the nematode Graphidioides affinis, specimens of which were found in captive Patagonian maras.